Statics and strength of materials for architecture and building construction - Onouye, Barry; Kane, Kevin 1954- (1999)
A valuable reference source, this richly illustrated, user-friendly text provides an informative introduction to structures and appeals to architectural and building construction students' strong need for visual reinforcement.